The effect of intradialytic food intake on hemodialysis adequacy and blood pressure; a quasi-experimental study - Shanki Goyal; Ashok Bhat; Sushanth Kumar (Journal of Nephropathology, 2024)
Introduction: Food intake during hemodialysis (HD) is a controversial issue. The potential benefits include improvement of nutritional status and patient satisfaction. However, the risks include the possibility of intradialytic hypotension (IDH) and dialysis inadequacy. There are no guidelines regarding food intake during HD. Objectives: To assess the impact of food intake during HD on IDH and dialysis adequacy. Patients and Methods: This was a single-center quasi-experimental study. Thirty patients undergoing regular maintenance HD were recruited for the study. The patients themselves served as their controls. In three separate sessions, they were assessed for IDH and dialysis adequacy (spKt/V, URR). The first session was without a meal, the second with a small meal, and the third with a large meal. Change in measured variables (spKt/V, URR) was assessed by repeated-measures analysis of variance (ANOVA). The McNemar test was conducted to compare the incidence of IDH between three different dialysis sessions. Results: Nine patients (30%) had IDH when they consumed a small meal (P=0.02, McNemar test), and eight patients had IDH (26.7%) when they consumed a large meal (P=0.03, McNemar test). The mean spKt/v and URR were not significantly different in the three sessions. Conclusion: There is a significantly increased risk of IDH due to food intake. IDH is associated with significant morbidity and mortality; hence, restricting food intake during HD sessions would be prudent.